2021
DOI: 10.17645/si.v9i1.3691
|View full text |Cite
|
Sign up to set email alerts
|

Choosing to Stay: Alternate Migration Decisions of Ghanaian Youth

Abstract: This article focuses on nationals from Ghana who have lost interest in pursuing migration dreams to Europe and North America after failed attempts to migrate. Many less experienced youths who attempt to migrate to Europe and North America face challenges such as strict immigration laws, high cost of financing migration plans, or illegal recruiters. Some risk their lives through dangerous routes to achieve their migration goals. The negative consequences recorded are numerous, including death en route to Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Terms such as "the age of immobility" or as "mobility bias" indicate a growing critique of the lack of analytical attention to immobility in the literature. While media narratives mainly portray a desperate desire of West African youth to reach Europe, studies have shown that half of adults in Sub-Saharan Africa do not wish to move to another country (Esipova et al, 2011;Setrana, 2021;see Schewel, 2015 for a study on Senegal).…”
Section: Changing Migration Aspirationsmentioning
confidence: 99%
“…Terms such as "the age of immobility" or as "mobility bias" indicate a growing critique of the lack of analytical attention to immobility in the literature. While media narratives mainly portray a desperate desire of West African youth to reach Europe, studies have shown that half of adults in Sub-Saharan Africa do not wish to move to another country (Esipova et al, 2011;Setrana, 2021;see Schewel, 2015 for a study on Senegal).…”
Section: Changing Migration Aspirationsmentioning
confidence: 99%
“…This article thus contributes to transnational migration studies that overlook stayer youth's agency and their ability to cope with and shape forces structuring their lives. While structural forces constrain or encourage youth's migration aspirations, youth demonstrate agency in aspiring to move, irrespective of whether such aspirations are realised and become actual migration (Carling & Schewel, 2018;de Haas, 2021;Setrana, 2021). Literature on stayer youth's aspirations has mainly emphasised that youth aspire to migrate because their parents reside abroad.…”
Section: Discussionmentioning
confidence: 99%
“…The aspiration‐ability framework introduced by Carling (2002) has been widely used to analyse immobility in migration studies (Setrana, 2021). de Haas (2010, 2021) further refined the framework by replacing ability with the capability to analyse how (im)mobility outcomes relate to development.…”
Section: The Aspiration‐capability Framework and Nonmigration Prefere...mentioning
confidence: 99%
“…The purpose of this article is to acknowledge the capability to stay and that migration aspirations may change over time and the life course. The mobility bias in migration theories focusing largely on those who migrate has left a gap in the migration literature related to why people stay, which calls for a deeper engagement with the process of choosing to stay (Setrana, 2021). This article seeks to contribute to filling this knowledge gap by focusing on Filipino nurses who, despite growing up in a culture of migration (Asis, 2006) and being trained in a profession and a system that is largely oriented towards overseas markets (Cabanda, 2017; Ortiga, 2021; Ortiga & Macabasag, 2021a, 2021b; Ortiga & Rivero, 2019), decided to stay in the Philippines.…”
Section: Introductionmentioning
confidence: 99%